Per-antenna signal to leakage noise ratio precoding for MU-MIMO-OFDM system with reduced feedback - Saeid, E. (Inderscience Enterprises Ltd., 2017)
In this work, multi-user multiple input multiple outputs orthogonal frequency division multiplexing (MU-MIMO-OFDM) precoding is introduced. The proposed method makes use of per-antenna signal to leakage plus noise ratio (PA-SLNR) as optimisation criteria. This optimisation criterion takes both the inter-user and inter-antennas interference cancellation into account. Unlike the conventional proposed methods in which simple frequency flat fading is assumed, in the proposed method we generalised the precoding problem to more realistic frequency selective MU-MIMO-OFDM Broadcast channel where OFDM is used to mitigate inter-symbol-interference (ISI) and the MU-MIMO is used for spatial multiplexing. Conventionally, each individual user has to feedback the channel frequency response of each subcarrier to the central node base station for precoding matrix design which leads to high traffic load in the feedback channel. In this work we also introduce a simple frequency response channel factorisation such that each user is required to feedback only one subcarrier time domain channel impulse response which dramatically reduces the amount of the feedback load. Copyright © 2017 Inderscience Enterprises Ltd.